Multi-pursuer pursuit differential game for an infinite system of second order differential equations - Kazimirova, R.Yu.; Ibragimov, G.I.; Hasim, R.M. (Udmurt State University, 2024)
We study a pursuit differential game of many pursuers and one evader. The game is described by the infinite systems of m inertial equations. By definition, pursuit in the game is completed if the state and its derivative of one of the systems are equal to zero at some time. In the literature, such a condition of completion of pursuit is also called soft landing. We obtain a condition in terms of energies of players which is sufficient for completion of pursuit in the game. The pursuit strategies are also constructed. © 2024 Udmurt State University. All rights reserved.